2008
DOI: 10.4161/cbt.7.8.6284
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34 mediates AR-dependent p53-induced apoptosis in prostate cancer

Abstract: We investigated whether knocking down AR expression effects apoptosis after treatment with different apoptosis-inducing agents. We found that siRNA AR (si-AR) significantly decreased apoptosis induced by topoisomerase inhibitors doxorubicin (DOX) and camptothecin (Campt). It is known that DNA double-strand break inducing agents leads to activation (phosphorylation) of p53 that in turn regulates the expression of a variety of apoptosis-related genes including microRNA(miR)-34a and 34b/c. We found that DOX induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
93
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(103 citation statements)
references
References 33 publications
6
93
0
3
Order By: Relevance
“…In addition, Myc could interact with miR-34b directly in the present study. miR-34 mediates androgen receptor-dependent p53-induced apoptosis in prostate cancer (39). The study by Corney et al confirmed that miR-34b Term, identification number of GO term or KEGG pathway; Description, name of GO term or KEGG pathway; Count, number of genes enriched in GO term or KEGG pathway.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, Myc could interact with miR-34b directly in the present study. miR-34 mediates androgen receptor-dependent p53-induced apoptosis in prostate cancer (39). The study by Corney et al confirmed that miR-34b Term, identification number of GO term or KEGG pathway; Description, name of GO term or KEGG pathway; Count, number of genes enriched in GO term or KEGG pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, it is mandatory to validate the expression of reference genes for each study design, as normalization to an unsuitable reference gene has been shown to lead to biased results (Dheda et al, 2005;Ohl et al, 2005). In the majority of miRNA expression studies, miRNAs or other small RNAs were used as reference genes, but some studies also normalized expression to longer mRNAs, namely GAPDH, TATA box binding protein mRNA, and RNAseP (Porkka et al, 2007;Huang et al, 2008;Place et al, 2008;Rokhlin et al, 2008;Gandellini et al, 2009). It is questionable as to whether mRNAs can be used as reference genes in miRNA expression studies, because longer RNAs may have different isolation efficiencies compared to miRNAs (Peltier and Latham, 2008), they may be degraded faster due to their length, and they are reverse transcribed with different techniques than the miRNAs of interest.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 16 articles (Jiang et al, 2005;Mattie et al, 2006;Porkka et al, 2007;Ambs et al, 2008;Josson et al, 2008;Mitchell et al, 2008;Ozen et al, 2008;Place et al, 2008;Prueitt et al, 2008;Rokhlin et al, 2008;Gandellini et al, 2009;Leite et al, 2009;Noonan et al, 2009;Siva et al, 2009;Spahn et al, 2009;Tong et al, 2009), in which miRNA RT-qPCR was performed. In 14 articles, relative quantification was performed and the reference genes utilized were specified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA-based treatment for human tumors has been documented extensively. The tumor suppressor role of mir-34 has been confirmed in vivo with these tumor xenografts via activation of the p53 pathway (16). The use of locked nucleic acid anti-mir-21 oligonucleotides has been reported to reduce the growth of U87 glioblastoma xenograft by >70% (17).…”
Section: Introductionmentioning
confidence: 92%